2021
DOI: 10.1007/s00345-021-03639-z
|View full text |Cite
|
Sign up to set email alerts
|

A novel prediction model for the completion of six cycles of radium-223 treatment and survival in patients with metastatic castration-resistant prostate cancer

Abstract: Purpose We evaluated the predictive factors for completion of all six cycles of radium-223 (Ra-223) treatment in patients with metastatic castration-resistant prostate cancer (mCRPC). We also developed a novel prediction model for Ra-223 treatment completion using these predictors. Methods We retrospectively reviewed data from 122 patients with mCRPC who were treated with Ra-223. The predictive factors for the completion of six cycles of Ra-223 treatment w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 16 publications
3
15
0
Order By: Relevance
“…In contrast, in Japan, all CRPC patients with bone metastases can be treated with Ra‐223. To complete six courses of Ra‐223 and thereby obtain an OS benefit, not a few bone metastatic CRPC patients in Japan receive Ra‐223 without waiting for two or more new AR inhibitors or DOC 7,10 . While there have been many reports on patients treated with Ra‐223 in Japan, none have described the improvement in the OS with Ra‐223 compared with a cohort not treated with Ra‐223 (Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, in Japan, all CRPC patients with bone metastases can be treated with Ra‐223. To complete six courses of Ra‐223 and thereby obtain an OS benefit, not a few bone metastatic CRPC patients in Japan receive Ra‐223 without waiting for two or more new AR inhibitors or DOC 7,10 . While there have been many reports on patients treated with Ra‐223 in Japan, none have described the improvement in the OS with Ra‐223 compared with a cohort not treated with Ra‐223 (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…While there have been many reports on patients treated with Ra‐223 in Japan, none have described the improvement in the OS with Ra‐223 compared with a cohort not treated with Ra‐223 (Table 2). 5–12 Therefore, in the present study, we investigated whether or not Ra‐223 improves the OS in Japanese patients using a large‐scale healthcare fee database.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite increasing clinical experience with Ra-223 given to mCRPC patients, clinical variables useful for predicting response to that radiopharmaceutical and also survival remain di cult to identify. Scoring systems reported include baseline Eastern Cooperative Oncology Group (ECOG) performance status, levels of hemoglobin, alkaline phosphatase (ALP), lactate dehydrogenase (LDH), and prostate speci c antigen (PSA), PSA doubling time (PSADT), completion of six cycles of Ra-223, as well as other factors [5][6][7][8][9][10][11][12][13][14][15]. However, a validated and simple model for clinicians to assess which patients will most likely bene t from Ra-223 treatment remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Many analyzed reports from several randomized controlled trials have shown that ureteroscopy achieved high success rates in managing ureteric stones and provided a better stone-free rate after treatment, fewer re-interventions, fewer sick leave days, and lower healthcare costs. However, compared to ESWL and PCNL patients, those who had undergone ureteroscopy, unfortunately, continue to have remnant stone fragments that may cause recurrent symptoms, obstruction, infection, and a longer hospital stay [ 30 , 31 ].…”
Section: Reviewmentioning
confidence: 99%